Avaliação da cultura de segurança do paciente na organização hospitalar do Hospital da Aeronáutica de Belém - SANTOS, Raísa Lamara Cruz dos (2019)
Through this, the idea of patient safety culture has been spreading and receiving more and more attention in the field of health organizations, being one of the essential requirements for improving the quality of patient care. Although it is a very relevant and current issue, it has not been much approached in Brazilian health institutions. Faced with the scarcity of specific studies related to the theme addressed to these institutions, and the importance of promoting a safety culture in these, we propose a study that seeks to obtain data and evidence that point out how the practice of health security has been applied in these Assessment of the performance of the activity in different sectors of the institution, the harmony among health professionals and the knowledge of each professional about the subject of patient safety in order to ensure that there is in fact a favorable safety culture or possible flaws that Can be corrected in favor of improving the patient's safety deficit. Thus, a cross-sectional, cross-sectional descriptive and cross-sectional epidemiological study will be carried out at the Aeronautical Hospital (HABE), with health professionals working at the Aeronautics Hospital of Belém, through the Application of the self-administered HSOPSC questionnaire adapted to the Brazilian reality.